Do institutional investors mitigate costly restructuring? Dynamic evidence from the globe - Muhammad Ashraf; Mubashar Ali; Ahmad Ghazali; Mubashar Tanveer (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2025)
This research aims to comprehensively examine the impacts of various levels of the life cycle stages of firms (LCSF) on restructuring charges and to investigate the impact of institutional ownership on the correlation between LCSF and restructuring charges. This study employs panel data that is run using a two-step system GMM. The dataset covers the years 2000 to 2023 and consists of 7,570 observations of firm-year of non-utility and non-financial companies. The results show that the charges of restructuring have the propensity to rise (or fall) as a firm moves to either growth or maturity (or introduction or decline) stage. Also, under institutional ownership, a firm changing to growth or maturity (or introduction or decline) stage leads to a significant increase (or minor decrease) in restructuring charges. The information on the correlation between LCSF and restructuring charges will assist the investors in forecasting the alterations in the restructuring costs as firms cross the various stages of their life cycles. Moreover, the effects of institutional ownership on this relationship will be useful in informing investors on how to best invest in stocks. To the best of our knowledge, no previous study has investigated the effects of LCSF on restructuring charges and the moderating effect of institutional ownership in the relationship. This research paper is aimed at filling this gap and offering new information.
Keywords: 330; large firms and small firms; firm life cycle stages; institutional ownership; Restructuring charges